2019
DOI: 10.1080/13696998.2019.1688821
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of rivaroxaban versus warfarin for stroke prevention in non-valvular atrial fibrillation in the Japanese healthcare setting

Abstract: Aims: This article aimed to examine the cost-effectiveness of rivaroxaban in comparison to warfarin for stroke prevention in Japanese patients with non-valvular atrial fibrillation (NVAF), from a public healthcare payer's perspective. Materials and methods: Baseline event risks were obtained from the J-ROCKET AF trial and the treatment effect data were taken from a network meta-analysis. The other model inputs were extracted from the literature and official Japanese sources. The outcomes included the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…A study carried out by Craig et al (2013) in the United States to compare the effectiveness and utility revealed that alteration of the treatment method and replacement of warfarin with rivaroxaban resulted in an increased QALY while bleeding decreased from 0.5 to 12.0. This is almost similar to the results of the study by Hori et al (2020) and Salcedo et al (2019) and Soyon et al (2013) [ 9 , 11 , 21 ]. Also, Wang et al (2014) calculated the cost-effectiveness of dabigatran and rivaroxaban in comparison with warfarin in patients with AF in Singapore.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A study carried out by Craig et al (2013) in the United States to compare the effectiveness and utility revealed that alteration of the treatment method and replacement of warfarin with rivaroxaban resulted in an increased QALY while bleeding decreased from 0.5 to 12.0. This is almost similar to the results of the study by Hori et al (2020) and Salcedo et al (2019) and Soyon et al (2013) [ 9 , 11 , 21 ]. Also, Wang et al (2014) calculated the cost-effectiveness of dabigatran and rivaroxaban in comparison with warfarin in patients with AF in Singapore.…”
Section: Discussionsupporting
confidence: 92%
“…The findings indicated that the treatment of AF patients with rivaroxaban and warfarin significantly decreased bleeding and stroke (81.9% vs. 44.4% for no bleeding and 98.6% vs. 95/7% for prevention of ischemic stroke). A study conducted by Hori et al (2020) in Japan found that rivaroxaban reduced the risk of ischemic stroke compared to warfarin, and this study confirms the results of our research [ 9 ]. In a study by Kleintjens et al, the cost-effectiveness of rivaroxaban compared with warfarin was calculated for prevention of stroke in AF patients in the Belgian health system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 16 Another study done in Japan among non-valvular atrial fibrillation patients for the treatment of stroke prevention identified that Rivaroxaban was cost-effective compared to warfarin (ICER= €24,446.42/QALY). 17 Even in different disease in US citizens, Warfarin is less cost effective compared with Apixaban for treatment of atrial fibrillation. Apixaban compared with Warfarin resulted in ICER of $53,925/QALY.…”
Section: Discussionmentioning
confidence: 99%